Internatonal Awards of the Virtual Archaeology, Tartessos Awards - Ioannides, Marinos (My University, 2026)
Internatonal Awards of the Virtual Archaeology, Tartessos Awards Prestigious international awards from the Spanish Society of Virtual Archaeology (SEAV). The award recognizes those members of the scientific community and institutions for their contribution to the dissemination and progress of Virtual Archeology worldwide. Since its foundation in June 2009 have been awarded to seventeen personalities, international researchers and three institutions.
Keywords: Sciences